Optimization of Switching Substation Performance for Power Network Stability Against Voltage Drop Effects at ULP Kutacane - Aldi Anggara; Dino Erivianto; Muhammad Erpandi Dalimunthe (Sean Institute, 2025)
This study aims to optimize the performance of the distribution substation in maintaining the stability of the electricity network, especially in reducing the effects of voltage drops in the Kuta-cane Customer Service Unit (ULP). Significant voltage drops can affect the quality of electricity supply and cause instability that impacts the performance of customers' electrical equipment. This study includes data collection on distribution substations and network conditions, voltage drop measurements at critical points in the network, and voltage distribution simulations using electrical analysis software. Based on the results of the analysis, optimization of the distribution substation was carried out by adjusting the transformer capacity, installing load balancing devices, and rearranging the load distribution to reduce voltage drops. The optimization results showed an increase in voltage stability in the Kuta-cane ULP electricity network, as indicated by a decrease in voltage drops in previously problematic areas. This optimization has proven effective in maintaining distribution stability and improving the quality of electricity supply to customers. This study produces technical recommendations that can be implemented by the Kutacane ULP in maintaining the performance of distribution substations sustainably, so as to improve the reliability of the electricity network in the region.